Pengaruh Penggunaan Model Pembelajaran Cooperative Learning Tipe STAD dan Tipe Jigsaw Terhadap Hasil Belajar Fiqih Kelas VIII Di MTs Muhammadiyah Blimbing Tahun Pelajaran 2015/2016 - Heriyanto, Heriyanto, Dr. M. Abdul Kholiq Hasan, M.A., M.Ed, Dr. Eko Supriyanto (2016)
This research aims to determine: (1) difference effect of using cooperative learning model STAD and Jigsaw type to learning outcome Fiqh class VIII MTs Muhammadiyah Blimbing the school year 2015/2016. (2) learning model with greater influence between learning model cooperative learning STAD and Jigsaw type to learning outcomes Fiqh class VIII MTs Muhammadiyah Blimbing the school year 2015/2016. This esearch included a quantitative study with an experimental model, the research subjects students of class VIII A and VIII C MTs Muhammadiyah Blimbing Polokarto Sukoharjo. The data collection technique using the techniques of tests and documentation. Test instrument used to test the validity and reliability. Data were analyzed using t-test technique which preceded the prerequisite test analysis, the test of normality and homogenity test. Based on data analysis with a significance level of 5% obtained thitung> ttable, namely 2.217> 2.003. Average value obtained between grade class that uses a learning model type STAD cooperative learning and classroom learning model cooperative learning using Jigsaw, which is 89.10345> 85.24138. The conclusion of this research are (1) there are difference effect of using operative learning model STAD and Jigsaw type to learning outcomes Fiqh class VIII MTs Muhammadiyah Blimbing the school year 2015/2016. (2) the use of cooperative learning model of STAD learning type greater influence than Jigsaw type on learning outcomes Fiqh class VIII MTs Muhammadiyah Blimbing the school year 2015/2016.